2011
DOI: 10.1590/s0004-282x2011000400010
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of P50 suppression deficit in patients with epilepsy and individuals with schizophrenia

Abstract: Objective: To identify P50 suppression in patients with epilepsy, to investigate the effect of seizure control on P50 suppression, and to compare epilepsy patients with individuals with schizophrenia and healthy volunteers. Method: P50 evoked potential parameters and P50 suppression were studied crossectionally in patients with uncontrolled or controlled epilepsy, in individuals with schizophrenia and in healthy volunteers. Results: Individuals with schizophrenia had significantly smaller conditioning stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This type of sensory suppression is usually observed in the auditory system by using paired-pulse suppression paradigms, in which two identical stimuli are successively presented, and is considered to represent processes that suppress redundant information. Such suppression is clinically important, because previous studies have shown deficits in paired-pulse suppression in patients with various conditions, including schizophrenia (Bramon et al 2004; Patterson et al 2008; Potter et al 2006; Turetsky et al 2007), bipolar disorder (Cheng et al 2016), epilepsy (Becker et al 2011), and attention-deficit/hyperactive disorder (Holstein et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This type of sensory suppression is usually observed in the auditory system by using paired-pulse suppression paradigms, in which two identical stimuli are successively presented, and is considered to represent processes that suppress redundant information. Such suppression is clinically important, because previous studies have shown deficits in paired-pulse suppression in patients with various conditions, including schizophrenia (Bramon et al 2004; Patterson et al 2008; Potter et al 2006; Turetsky et al 2007), bipolar disorder (Cheng et al 2016), epilepsy (Becker et al 2011), and attention-deficit/hyperactive disorder (Holstein et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Paired pulse suppression, an electrophysiological measurement of cortical responses to 2 consecutive identical auditory stimuli spaced 500 ms apart [ 9 , 10 ], is used to detect long-latency suppression, in which the amplitude of an evoked response at approximately 50 ms (P50) is compared between the first and second stimuli. This measurement technique is clinically important, as previous studies have shown deficits in paired-pulse suppression in patients with schizophrenia [ 10 14 ], bipolar disorder [ 15 ], panic disorder [ 16 ], epilepsy [ 17 ], and attention-deficit/hyperactive disorder [ 18 ]. In addition, paired-pulse suppression is also related to increased risk for developing schizophrenia [ 19 ] as well as deficits in attention processing in schizophrenia [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our paradigm may be useful for evaluating inhibitory function in individual subjects in clinical situations, because many diseases such as epilepsy [ 17 ] are considered to cause deficits in inhibitory mechanisms. However, it remains unclear whether inhibition of a specific auditory system reflects the fundamental functions of inhibitory circuits in an individual, as only a few studies have evaluated the relationships among auditory and sensory systems in healthy subjects [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was reported that positive symptoms of schizophrenia, such as auditory hallucinations [7, 8], and also the risk for developing schizophrenia [9] have a relationship to impairment of P50 suppression. Other clinical conditions also known to be related to impairment of sensory suppression include bipolar disorder [10], panic disorder [11], epilepsy [12], and attention-deficit/hyper-active disorder [13]. Hence, P50 suppression deficit has been speculated to be associated with varied cognitive impairments in a wide range of disorders and their symptoms.…”
Section: Introductionmentioning
confidence: 99%